Upaya Meningkatkan Hasil Belajar Matematika Peserta Didik Melalui Model Pembelajaran Kooperatif Tipe Stad Materi Lingkaran di Kelas VI SD Negeri 215/X Sungai Toman Semester Ganjil Tahun Pelajaran 2022/2023 - Elfina Elfina (Journal on Education, 2022)
This study aims to describe and obtain information on improving mathematics learning outcomes through the STAD type cooperative learning model. This research is a classroom action research which consists of two cycles, each cycle consists of two meetings. Each meeting consists of four stages, namely planning, implementation, observation and reflection. The subjects of this study were students of class VI SDN 215/X Sungai Toman, totaling 21 people. This research was conducted in the odd semester of the 2022/2023 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that the STAD type cooperative learning model can improve the mathematics learning outcomes of sixth grade students at SDN 215/X Sungai Toman by giving rewards.